Political Selection and the Concentration of Political Power - Andreas Grunewald; Emanuel Hansen; Gert Pönitzsch (University of Bonn, Bonn Graduate School of Economics (BGSE), 2015)
This paper studies the effects of power-concentrating institutions on the quality of political selection, i.e., the voters' capacity to identify and empower well-suited politicians. In our model, candidates are heterogeneous in two unobservable quality aspects: ability and public-spiritedness. As voters can only base their ballots on the candidates' binding policy proposals, low-quality candidates face incentives to mimic their high-quality counterparts and a selection problem arises. We nd that powerconcentrating institutions amplify this selection problem as they increase electoral stakes and thus the incentives for mimicking. However, they also allocate more political power to the voters' preferred candidate. As a consequence, the optimal institutional setting depends on the con ict of interest between voters and candidates. The larger the con ict of interest, the smaller is the level of power concentration that maximizes voter welfare. A complete concentration of power in the hands of the election winner is optimal if and only if the con ict of interest is small.
Keywords: D72; D82; H11; 330; Elections; Constitutional Design; Selection; Asymmetric Information